Tumor-initiating cells are not enriched in cisplatin-surviving BRCA1;p53-deficient mammary tumor cells in vivo - Pajic, Marina (Landes Bioscience, 2010)
Although many breast cancers respond to chemotherapy or hormonal therapy, lack of tumor eradication is a central clinical problem preceding the development of drug-resistant tumors. Using the K14cre;Brca1(F5–13/F5–13);p53(F2–10/F2–10) mouse model for hereditary breast cancer, we have previously studied responses of mammary tumors to clinically relevant anti-cancer drugs, including cisplatin. The BRCA1- and p53-deficient tumors generated in this model are hypersensitive to cisplatin and never become resistant to this agent due to the large, irreversible deletion in Brca1. We show here that even dose-dense treatment with a maximum tolerated dose of cisplatin does not result in complete tumor eradication. To explain this result we have addressed the hypothesis that the lack of eradication of drug-sensitive tumors is due to increased in vivo chemotherapy resistance of tumor-initiating cells (TICs). Using the CD24 and CD49f cell surface markers that detect normal mouse mammary stem cells, we have identified tumor-initiating cells in BRCA1- and p53-deficient tumors. In addition to the Lin(−)/CD24(+)/CD49f(+) subpopulation, we show that a larger population of Lin(−)/CD24(+)/CD49f cells also has tumor-initiating capability in at least two serial orthotopic transplantations, suggesting that these are not more differentiated transit-amplifying cells. However, we did not find an enrichment of TICs in cisplatin-treated tumor remnants. We conclude that in this model the tolerance of the cisplatin-surviving cells cannot be attributed to special biochemical defense mechanisms of TICs.